Manufacturing Analysis of Anti-shedding Shampoo from Ambon Banana Peel Extract and Tea Leaf Extract (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
This research aims to make environmentally friendly shampoo products from natural waste. The waste used is ambon banana peel with variations of green tea leaves. The choice of ambon banana peel as the essential ingredient for making shampoo is motivated by the problem of banana peel waste, which has many properties but needs to be correctly utilized by the community. The method used in this research is maceration extraction. The Extract was then subjected to a phytochemical screening test, after which it was mixed in a shampoo preparation and tested for its characteristics. Based on the experiment results, the shampoo made from ambon banana peel waste and tea leaves showed positive characteristic test results and was safe to use to overcome hair loss problems. The viscosity measurement results show that the second and third formulations are optimal because they are within the viscosity range of 446 cp and 767 cp.